Resource Recovery Potential From Lignocellulosic Feedstock Upon Lysis With Ionic Liquids - Padrino, Beatriz; Lara-Serrano, Marta; Morales-delaRosa, Silvia; Campos-Martín, José M.; Fierro, José Luis García; Martínez, Fernando; Melero, Juan Antonio; Puyol, Daniel (Frontiers in Bioengineering and Biotechnology, 2018)
Lignocellulosic residues from energy crops offer a high potential to recover bioproducts and biofuels that can be used as raw matter for agriculture activities within a circular economy framework. Anaerobic digestion (AD) is a well-stablished driver to convert these residues into energy and bioproducts. However, AD of lignocellulosic matter is slow and yields low methane potential, and therefore several pre-treatment methods have been proposed to increase the energy yield of this process. Hereby, we have assessed the pre-treatment of lignocellulosic biomass (barley straw) with the ionic liquid (IL) 1-ethyl-3-methylimidazolium acetate and its effect on the biochemical methane potential (BMP). The BMP of the residue was evaluated at different inoculum to substrate (I/S) ratios and working under meso and thermophilic conditions. Solids destruction upon AD is highly enhanced by the IL-pretreatment. This also resulted in a higher BMP, both in mesophilic as well as thermophilic conditions. At the optimum I/S ratio of 2:1 (dried weight, dw), the BMP of the IL-pre-treated feedstock increased 28 and 80% for 35 days of thermophilic and mesophilic AD, respectively, as compared to the fresh feedstock, achieving values of 364 and 412 LCH4/kgTS. We also explored the effect of this pretreatment on the phosphorus recovery potential from the digestate upon release from the AD process. Thermophilic anaerobic digestion of IL-pre-treated biomass provided the highest P recovery potential from lignocellulosic residues (close to 100% of the theoretical P content of the lignocellulosic feedstock). Therefore, the pretreatment of lignocellulosic feedstock with IL before AD is a promising platform to obtain bioenergy and recover P to be regained for the agriculture sector.